MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Supriyanto Supriyanto (Jurnal Inovasi Sekolah Dasar, 2020)
AbstractThis research is a class action study conducted in two cycles. The purpose of this research is to increase the activation and learning results of mathematics on the competency of FPB and KPK in class IV (four) of SDN 14 Indralaya Utara, Ogan Ilir Regency, South Sumatera Province, through the application of a Teams type cooperative learning model Games Tournament (TGT). Each cycle consists of four phases: planning, implementation, observation, and reflection. The subject of this study amounted to 24 students. The instruments used in this study include an active observation sheet for students ' learning and test to learn students ' learning outcomes. Cessation of cycles based on research success indicators of 96% positive activation and 4%, negative activity. And obtained 100% learning results reached KKM 65. Based on the research results, it was concluded that the application of the Teams Games Tournament (TGT) cooperative learning model could improve the activity and learning outcomes of mathematics students on the competence of FPB and KPK. Keywords:  Cooperative learning Model, Teams Games Tournament Abstrak. Penelitian ini merupakan penelitian tindakan kelas yang dilakukan dalam dua siklus. Tujuan penelitian ini untuk meningkatkan keaktifan dan hasil belajar matematika pada kompetensi FPB dan KPK di kelas IV (empat) SDN 14 Indralaya Utara, Kabupaten Ogan Ilir, Propinsi Sumatera Selatan, melalui penerapan model pembelajaran kooperatif tipe Teams Games Tournament (TGT). Setiap siklus terdiri dari empat tahapan yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini berjumlah 24 siswa. Instrumen yang digunakan dalam penelitian ini meliputi lembar observasi keaktifan belajar siswa dan test untuk mengetahui hasil belajar siswa. Penghentian siklus berdasarkan indikator keberhasilan penelitian sebesar 96% keaktifan positif dan 4%, kaaktifan negatif. Serta diperoleh hasil belajar 100% mencapai KKM 65. Berdasarkan hasil penelitian, disimpulkan bahwa penerapan model pembelajaran kooperatif tipe Teams Games Tournament (TGT) dapat meningkatkan keaktifan dan hasil belajar siswa matematika pada kompetensi FPB dan KPK. Kata Kunci. Model pembelajaran kooperatif, Teams Games Tournament